Crime in New Orleans: applying the civic community perspective to urban violence - Doucet, Jessica M. (2011)
Civic community theory is a macro-level social control perspective that has emerged within the past 10 years as an explanation of community variation in crime rates. The theory is based on the assumption that well-integrated communities are better able to regulate their members’ behaviors than poorly integrated communities. It has been particularly successful in explaining violent crime rates in rural counties or communities, but research has generally ignored the relationship between civic community theory and violent crime in urban areas. The current study aims to determine the applicability of the civic community perspective to urban areas, as a link has not been demonstrated in previous research. To test its applicability, census tract data are analyzed. The link between civic community theory and violent crime, particularly homicide and aggravated assault, is determined using secondary data geocoded to census tracts in Orleans Parish, Louisiana. Data are gathered from the U.S. Census Bureau’s American Community Survey, the Zip Code Business Patterns, and the New Orleans Police Department. Negative binomial regression techniques are utilized after creating a measure to capture any spatial autocorrelation that may exist between census tracts. The results reveal that the protective effects of civic community theory are applicable to violent crime in urban areas. Each civic community measure was found to be negative and significantly related to homicide and aggravated assault counts individually and when combined. Additionally, an interactive effect between civic engagement and resource disadvantage indicated that the protective effect of civic engagement is stronger in areas plagued with high levels of disadvantage. Upon analyzing the standardized percent changes, it was revealed that the strength of the individual civic community measures varies depending on which violent crime is being predicted. Specifically, self-employment was found to have a greater protective effective against homicide while civic engagement and homeownership had greater protective effects against aggravated assault. The paper is concluded with a discussion of theoretical implications, limitations of the current project, and avenues for future research